Click, Sell, Grow: The Moderating Role of Government Policy on Social Media Marketing and MSME Performance in Indonesia (A TAM-Based SEM Study) - Fiona, Febzi; Daulay, M. Yasser Iqbal; Hayadi, Ilsya (Indonesian Journal of Business and Entrepreneurship, 2026)
Background: Promotion in today’s digital era must keep pace with rapid developments, yet many MSMEs still face limited competence and organizational readiness to adopt social media-based digital marketing. These constraints make it important to understand how government policy can shape MSME outcomes in Indonesia. Purpose: This study analyzes the role of government policy in influencing the relationship between social media-based digital marketing and MSME performance in Indonesia. Design/Methodology/Approach:This research employed a quantitative survey of 500 MSME owners/managers who use social media for marketing in selected Indonesian provinces. The questionnaire used a Likert scale, the data were transformed using the Successive Interval Method, and the model was tested using Structural Equation Modeling with AMOS to examine perceived ease of use, perceived usefulness, attitudes toward social media use, actual social media use, government policy, and MSME performance, including government policy as a moderating variable. Finding/Result: Perceived ease of use and perceived usefulness positively affect attitudes toward social media use, and these attitudes positively influence actual social media use. Actual social media use improves MSME performance, while government policy also directly improves MSME performance; moreover, government policy strengthens the influence of social media use on MSME performance, indicating that supportive policies enhance the conversion of social media marketing adoption into business outcomes. Conclusion: Government policy strengthens the impact of social media-based digital marketing on MSME performance in Indonesia, suggesting that institutional support amplifies the benefits of technology adoption among MSMEs. Originality/Value (State of The Art): This study integrates government policy as a moderating variable in a TAM-based SEM framework to help explain inconsistent findings on the performance outcomes of social media adoption among MSMEs in developing economy contexts. Keywords: digital marketing, government policy, MSME performance, social media, technology adoption